Investigation on dielectric response of PMN ceramics around paraelectric-ferroelectric diffuse phase transition - Guerra, J. D. S.; Araujo, E. B. [UNESP]; Guarany, C. A. [UNESP]; Lima, E. C. [UNESP] (Maney Publishing, 2009)
The dielectric properties of relaxor ferroelectric lead magnesium niobate Pb(Mg(1/3)Nb(2/3))O(3) (PMN) ceramics have been investigated. These studies were conducted taking into account the characterisations of the complex dielectric permittivity (real and imaginary parts) as a function of temperature and frequency in a wide interval. on the other hand, the dc 'bias' electrical field dependence of the real dielectric permittivity (C-V characterisations) has been analysed around the paraelectric-ferroelectric diffuse phase transition. Results obtained at room temperature (paraelectric phase) showed a typical behaviour of conventional dielectric materials, while measurements performed at 200 K (ferroelectric phase) evidenced an anomalous behaviour for frequencies up to 100 kHz. Such observed anomalies were characterised by two asymmetrical peaks on sweep-up and sweep-down, at -15 and +18 kV cm(-1) respectively.
Keywords: Ferroelectrics; Relaxors; Phase transition; PMN